AI in Social Determinants of Health Analysis and Intervention: A New Frontier in Health Equity - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2025)
AI in Social Determinants of Health Analysis and Intervention: A New Frontier in Health Equity The Social Determinants of Health (SDoH)—the conditions i...
Keywords: Digital Health; Artificial Intelligence; Machine Learning; Medical Ethics; Healthcare Data